2015
DOI: 10.1002/rra.2874
|View full text |Cite
|
Sign up to set email alerts
|

A Multimetric Macroinvertebrate Index for the Implementation of the European Water Framework Directive in French Guiana, East Amazonia

Abstract: Neotropical, overseas regions of Europe are subjected to the same water policy objectives as the continental ones but were overlooked during recent developments of bioindicators that fulfil the Water Framework Directive guidelines. We designed a macroinvertebrate-based multimetric index [Indice Biotique Macroinvertébrés de Guyane (IBMG)] to assess ecological health in remote headwater-small streams of French Guiana, Europe's only overseas region of continental South America. Invertebrates were sampled at 95 si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Nevertheless, in the last 20 years a considerable amount of information has been produced in South and Central America on the ecology, biodiversity and response of organisms to environmental stressors in rivers [ 108 ] such as in: Uruguay [ 109 ]; Paraguay [ 110 ]; Bolivia [ 111 ]; Chile [ 112 ]; Colombia [ 113 ]; Peru [ 114 ]; Ecuador [ 115 ]; Guiana Francesa [ 116 ]; Venezuela [ 117 ]; Brazil [ 118 , 119 ]. Most studies were conducted based on a single or few temporal samplings with some exceptions covering multiple years, such as in studies of the Rio das Velhas basin, Minas Gerais, Brazil [ 120 , 121 ].…”
Section: Biological Assessment Of Riversmentioning
confidence: 99%
“…Nevertheless, in the last 20 years a considerable amount of information has been produced in South and Central America on the ecology, biodiversity and response of organisms to environmental stressors in rivers [ 108 ] such as in: Uruguay [ 109 ]; Paraguay [ 110 ]; Bolivia [ 111 ]; Chile [ 112 ]; Colombia [ 113 ]; Peru [ 114 ]; Ecuador [ 115 ]; Guiana Francesa [ 116 ]; Venezuela [ 117 ]; Brazil [ 118 , 119 ]. Most studies were conducted based on a single or few temporal samplings with some exceptions covering multiple years, such as in studies of the Rio das Velhas basin, Minas Gerais, Brazil [ 120 , 121 ].…”
Section: Biological Assessment Of Riversmentioning
confidence: 99%
“…Although several macroinvertebrate indices enabling the biological evaluation of freshwater ecosystems are available (e.g. Couceiro et al 2012;Dedieu et al 2016), these are seldom used because to our knowledge, there is currently no environmental law or regulation relying on these in this ecoregion. One exception in that respect is French Guiana, which must comply with the European Water Framework Directive.…”
Section: In Aquatic Ecosystemsmentioning
confidence: 99%
“…in Thailand; Boonsoong et al, 2008). Recent studies conducted in tropical areas showed that family-level resolution successfully detect anthropogenic impairment (Dedieu et al, 2015). However, genus-level would have provided more accurate information on water integrity (Lenat & Resh, 2001) and on environmental factors influencing communities (e.g.…”
Section: Discussion -Conclusionmentioning
confidence: 99%